2015
DOI: 10.1016/j.homp.2015.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Experimental physical methods and theories – then and now

Abstract: Grant challenges in science often take a more targeted and more concerted approach to formulate a research question and then look for answers. A concerted effort to focus on one hypothesized physical aspect of a well-defined homeopathic preparation may help aligning experimental methods with theoretical models and, in doing so, help to gain a deeper understanding of the whole body of insights and data produced.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
(21 reference statements)
0
2
0
Order By: Relevance
“…Jurgen Schulte, also an author in 1994, 1 reported on experimental physical methods and theories for investigating UHDs. 16 His contribution in 1994 had reported on research on ice crystal structures of UHDs, nano-scale effects of succussion, clathrate structures, isotopic selforganisation, electromagnetic superradiance and coherent states as described in quantum physics, including implications of spectroscopy (UV, X-ray, Raman) and nuclear magnetic resonance experiments. New developments were outlined, with special emphasis on non-local entanglement theory.…”
Section: Part 3 (Physics)mentioning
confidence: 99%
See 1 more Smart Citation
“…Jurgen Schulte, also an author in 1994, 1 reported on experimental physical methods and theories for investigating UHDs. 16 His contribution in 1994 had reported on research on ice crystal structures of UHDs, nano-scale effects of succussion, clathrate structures, isotopic selforganisation, electromagnetic superradiance and coherent states as described in quantum physics, including implications of spectroscopy (UV, X-ray, Raman) and nuclear magnetic resonance experiments. New developments were outlined, with special emphasis on non-local entanglement theory.…”
Section: Part 3 (Physics)mentioning
confidence: 99%
“…New developments were outlined, with special emphasis on non-local entanglement theory. 16,17 Following a classification scheme by Becker-Witt et al 18 Schulte classified studies according to publication quality 19 and concluded that the body of knowledge is promising but requires a concerted action if it is to lead to field. In an update on preliminary elements of a theory on UHDs 20 Schulte and Endler re-addressed questions surrounding different mechanisms of (i) interaction between the molecular mother substance and the solvent, (ii) storage of molecule-specific information in the solvent, (iii) physiological basis of the sensitivity of the living organism towards an UHD and (iv) interaction of the test dilution with the organism.…”
Section: Part 3 (Physics)mentioning
confidence: 99%